RabbitMQ essentials : hop straight into developing your own messaging applications by learning how to utilize RabbitMQ - Dossot, David (Community experience distilled., 2014)
In Detail With the advent of cloud computing, the need to design and build applications that can meet the demand and complexity of the modern world has never been greater. RabbitMQ is above all other forms of Message Queuing software thanks to its loosely coupled architecture and its ability to bind multiple languages, making modern web applications secure, scalable, and simple to maintain. However, in order to implement the best design and development practices when developing your messaging applications, you will need proper guidance on how to use RabbitMQ effectively. Armed with this supportive guide, you now have the opportunity to get immediately stuck into developing your own message-based applications with RabbitMQ. Using the fictitious Clever Coney Media as a case study, you will follow their journey of developing with RabbitMQ; from implementing simple, synchronous get operations to using advanced message routing and tracking the messaging application. With RabbitMQ Essentials, you get to observe how using Message Queuing software can streamline the development of your own distributed and scalable applications. Once you have familiarized yourself with the RabbitMQ setup, you will soon be creating your own inbox to send and receive messages through the combination of user-specific queues as well as bound and direct exchanges. After extending your messaging system by developing your own public address system, you will learn how to analyze traffic through your own application using a Python client. If you have ever feared losing messages, prepare to be amazed once you discover how to deal with dead letters and message rejection. To round off this crash-course in RabbitMQ, you will finally learn how to track your application and prevent something disastrous occurring to it. With so many other Message Queuing software available to you, RabbitMQ Essentials will show you precisely why RabbitMQ is leaps and bounds above the rest when it comes to building your own message-driven applications. Approach This book is a quick and concise introduction to RabbitMQ. Follow the unique case study of Clever Coney Media as they progressively discover how to fully utilize RabbitMQ, containing clever examples and detailed explanations. Who this book is for Whether you are someone who develops enterprise messaging products professionally or a hobbyist who is already familiar with open source Message Queuing software and you are looking for a new challenge, then this is the book for you. Although you should be familiar with Java, Ruby, and Python to get the most out of the examples, RabbitMQ Essentials will give you the push you need to get started that no other RabbitMQ tutorial can provide you with.